2017
DOI: 10.1212/wnl.0000000000004537
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic complications of sickle cell disease in Africa

Abstract: Objective:To summarize prevalence data on the neurologic complications of sickle cell disease (SCD) in Africa.Methods:We searched EMBASE, PubMed, and African Index Medicus to identify all relevant articles published from inception to May 31, 2016. Each study was reviewed for methodologic quality. A random-effects model was used to estimate the prevalence of neurologic complications of SCD across studies.Results:Thirty-one studies were included. Methodologic quality was high or moderate in 90% of studies. Strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 50 publications
4
47
0
Order By: Relevance
“…Our estimate of stroke prevalence is similar to that reported in a recent review of SCD stroke combining children and adults across Africa. 12 Similar to our findings, they also reported a higher stroke prevalence in studies utilizing diagnostic imaging and clear diagnostic criteria. Our systematic review and meta-analysis summarize what is known about pediatric SCD stroke in SSA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our estimate of stroke prevalence is similar to that reported in a recent review of SCD stroke combining children and adults across Africa. 12 Similar to our findings, they also reported a higher stroke prevalence in studies utilizing diagnostic imaging and clear diagnostic criteria. Our systematic review and meta-analysis summarize what is known about pediatric SCD stroke in SSA.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study reviewing neurologic complications of SCD in Africa highlights the interest in this area of research. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…When deoxygenated, hemoglobin S (HbS) polymerizes to form a fibrous network responsible for red cell rigidity, hemolysis, increased blood viscosity, poor microvascular blood flow and vessel occlusion [ 3 ]. Acute and chronic vessel occlusion could cause significant complications in various organs including the brain (strokes or silent brain infarcts), the kidneys (renal infarction with papillary necrosis or medullar fibrosis), the bones (aseptic osteonecrosis, pain crises), the spleen (spleen infarcts), the retina (retinopathy), the lungs (acute chest syndrome) or the male external genitalia (priapism) [ 3 5 ]. Some studies have also suggested an increased risk of venous thromboembolism (VTE) in patients with SCD or sickle cell trait (SCT) [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sickle cell disease (SCD) remains the leading cause of stroke in Black children. 1,2 Nigeria has the largest burden of SCD in the world, with about 150,000 babies born annually with the disorder. 3,4 Hospitalbased studies have reported stroke prevalence rates of 6-8% in Nigerian children with SCD.…”
Section: Introductionmentioning
confidence: 99%